The Analysis of the Redesign of the Rice Storage Warehouse Layout Using the Shared Storage Method at PT. XYZ - Awwali, Fariq; Widjajati, Endang Pudji (Science and Technology Research Centre Universitas PGRI Semarang, 2024)
In the manufacturing industry, problems often occur with warehouse layout arrangements. A finished product warehouse that is not arranged based on a good warehouse layout designer will experience difficulties in operating the product entry and exit process and is not based on the capacity of the warehouse itself. Increasingly advanced industry and increasingly fierce business competition encourage. The problems that occurred in the 4C Warehouse of the PT.XYZ Complex were in the storage warehouse and the placement of rice, causing several problems in the process of loading and unloading goods. PT.XYZ uses the Shared Storage method to arrange the warehouse space layout using the FIFO (First In First Out) principle, namely where products that are quickly sent are placed in the storage area closest to the entrance and exit. Data collection was carried out through observation, interviews and literature study. Data is calculated and analyzed by comparing the total distance of the initial layout and the proposed layout. The research results show that the total distance of the proposed layout is smaller than the initial layout with a total distance of 617,7.